CORRELATION OF EXCESS FREE ENERGY AND EXCESS MOLAR POLARIZATION IN BINARY MIXTURES USING POLAR-POLAR AND POLAR-NON POLAR INTERACTION - RANJITA MAHAPATRA; S. K. RAY (International Journal of Pharma and Bio Sciences, 2013)
Excess free energy of mixing and excess molar polarization in the binary mixtures of alcohols in non polar solvents like n-pentane, n-hexane, n-heptane and cyclohexane are evaluated considering polar-polar interaction only and polar-polar interaction with polar-non polar interaction. The important observation obtained from the calculation of excess free energy and excess molar polarization clearly indicates that polar-non polar interaction in comparison to polar-polar interaction bears a major role. The decrease in excess free energy after 0.2 mole fraction of polar liquids is due to the formation of domain barriers of non polar molecules in polar molecules which prevents the induced spontaneous polarization in polar liquids. The excess free energy and excess molar polarization is more in n-pentane and n-heptane as induced polarization plays a vital role due to the presence of an odd number of carbon atoms in n-pentane and n-heptane.